Roles of local food and knowledge of indigenous communities during pandemic COVID-19 at three districts across West Papua Province, Indonesia (Asian Journal of Ethnobiology, 2024)
Abstract. Wahyudi, Djitmau DA, Dwiranti F, Sagrim M, Manuhua D. 2024. Roles of local food and knowledge of indigenous communities during pandemic COVID-19 at three districts across West Papua Province, Indonesia. Asian J Ethnobiol 7: 1-12. The world suffered from the COVID-19 pandemic without exception to local communities in West Papua Province, causing deaths worldwide. During the pandemic, food supply, availability, and distribution were short. Indigenous communities in West Papua Province, Indonesia are surrounded by natural resources providing foods, vegetables, vitamins, and other nutrients for maintaining the human immune system. This research was designed to determine local food diversity, examine the contribution of local foods in fulfilling daily needs, nutrient sources, medicines, and others during the pandemic, and document local community perception of the pandemic COVID-19 among three study areas in West Papua Province. A questionnaire field survey was employed for data collection: 11 villages at three districts in Manokwari, South Manokwari, and Teluk Bintuni were selected to represent coastal, lowland, and mangrove areas. The results indicated that local food provides all daily food needs, offering various ingredients and supporting the livelihood of the local communities. Among the three districts, there are variations in food diversity, but they are similar. Furthermore, 18 plants were consumed as vegetables; 14 plants as carbohydrate sources; 16 plants for fruits, medicinal, herbs, respectively; 13 plants for flavor; Protein and fat-producing plants and animals were 7 of plants and 6 of animal, respectively. They were prepared by boiling, fresh, roasted, burned in a wood fire, and fried gently with cooking oil. These local foods are also the source of house income, offer informal work, and are a source of medicinal plants. When food supply and distribution are scarce everywhere due to the COVID-19 pandemic, the local communities rely on their local foods to maintain their health and immunity. They believe that the COVID-19 virus is a warning from God to humans who always exploit nature without caring for others.
Keywords: COVID-19, local food and knowledge, West Papua